Pelaksanaan Diyat Dalam Kerangka Perundangan Di Malaysia: Cabaran Fiqh Semasa - Ismail, Paizah (Jurnal Fiqh, 2012)
Diyat, or ?Blood Money? is a sum to be paid by the criminal or his family in cases of ?Qisas and Diyat?, which generally concerns ?Murder or causing bodily harm?. However, the implementation of this law seems very difficult, if not impossible these days due to the change in values and society. This article analyses the way how to overcome these problems by a method known among some Islamic Scholars as ?Contemporary Islamic Jurisprudence?. Among the findings of this study are, even though the word of Allah and the sayings of Prophet Muhammad are absolute and universal the interpretations of the jurists on the verses and hadith are not the same. It has always been influenced, among others, by the realities of life according to the time and location. Therefore, to implement such laws nowadays the classical juristic on the related verses of the Quran and the hadith of the Prophet Muhammad should be revisited by taking into account the reality of current life and society.